Enhancing student engagement through role-playing: A study on reproductive system education in class IX E at SMP Negeri 5 Pontianak - Kartikasari, Euis (IKIP PGRI Pontianak, 2024)
This study was conducted to determine the improvement in student activity and learning outcomes on the topic of the reproductive system in Class IX E at SMP Negeri 5 Pontianak. The objective of this research is to investigate the enhancement of student engagement and learning outcomes using the role-playing method. This classroom action research was carried out in two cycles. Data were collected through observation and tests. The results indicated an increase in student learning activities from 67.95% in the first cycle to 88.82% in the second cycle, as well as an improvement in learning mastery from 45.94% to 78.37%. Therefore, the role-playing method has proven to be effective in enhancing student activity and learning outcomes.